The Effect of Abdominal Stretching on Menstrual Cramps (Dysmenorrhea) Among Female Teenagers at SMPN 2 Purwodadi - Diva Aulia Roisyabillah; Naimah Naimah (Journal of Social Research, 2026)
Dysmenorrhea is one of the reproductive health problems that are commonly experienced by adolescent girls and can interfere with activities and quality of life. The high prevalence of dysmenorrhea indicates the need for safe and easy-to-apply nonpharmacological interventions. One method that can be used is Abdominal Stretching which functions to relax muscles and increase blood circulation so as to help reduce pain. This study aims to determine the effect of Abdominal Stretching on menstrual pain (dysmenorrhea) in adolescent girls at State of Junior High School 2 Purwodadi. Using a pre-experimental design with a one group pretest-posttest approach. The population in this study is 64 female students with a sample of 56 respondents obtained using the quota sampling technique. Pain level was measured using the Verbal Descriptor Scale (VDS) and analyzed using the Wilcoxon Signed-Rank Test. The study showed that most of the respondents experienced a decrease in pain levels after being given the Abdominal Stretching intervention, with 83.9% of respondents experiencing a decrease in pain and no increase in pain. The results of the statistical test showed a value of Z = -6.171 with a p-value of < 0.001 (p < 0.05), which means that there was a significant difference between the level of pain before and after the intervention. That Abdominal Stretching has a significant effect in reducing menstrual pain (dysmenorrhea) in adolescent girls, so that it can be used as an alternative to non-pharmacological treatment that is effective and easy to do independently